PENGARUH GENDER DIVERSITY DAN GOOD CORPORATE GOVERNANCE TERHADAP UNDERPRICING PADA PERUSAHAAN NON – KEUANGAN YANG MELAKUKAN IPO PERIODE 2006-2016 - Kevin Kurniawan; Deddy Marciano; Arif Herlambang (CALYPTRA, 2018)
This study aimed to analyse factors affecting underpricing for non-finance companies that indicated their first public offering during 2006-2016. Independent variables used are percentage of woman director, underwriter prestige, percentage outside director, ownership concentration, institutional ownership, and profitability. This study uses a quantitative approach with multiple linear regression as analysis model. This study uses a sample of non-finance firms that initiated their first public offering on 2006-2016. Number of observations used in this study is 78 observations. The results showed the percentage of female directors, prestige underwriters, percentage of outside directors, ownership concentration, and significant profitability against underpricing on the first day (1st day of return and abnormal return day 1) on stock prices in the secondary market. Then this research also shows the rebustness check result of underpricing on the seventh day (7th return and 7th abnormal return day) and thirty (30th return day and 30th abnormal return).